The Influence Of Digital Technology Adoption, Product Innovation, And Fiscal Policy On The Performance Improvement Of Micro, Small, And Medium Enterprises (MSMES) In The Digital Economy Era In East Kalimantan - Tommy Fimi Putera, Muhammad; Hwihanus, Hwihanus; Harits Zidni Khatib Ramadhani, Muhammad (Citakonsultindo, 2025)
This study aims to analyze the influence of digitalization, innovation, and fiscal policy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in East Kalimantan Province.1 The background of this research is based on the importance of digital transformation and government fiscal policy support in enhancing the competitiveness and productivity of MSMEs in the modern economic era.1 The research method used is quantitative with a multiple linear regression approach.1 Data were obtained by distributing questionnaires to 120 MSME actors in several regencies/cities in East Kalimantan.1 The analysis results indicate that the variables of digitalization (X₁), innovation (X₂), and fiscal policy (X₃) have a positive and significant influence on MSME performance (Y), both partially and simultaneously.1 The t-test shows that all three variables have a significance value of < 0.05, while the F-test results show an F-statistic of 45.762 with a significance of 0.000, indicating that the regression model is simultaneously significant.1 The coefficient of determination (R²) value is 0.685, which means that 68.5% of the variation in MSME performance can be explained by these three variables, while the remaining 31.5% is influenced by other factors outside the model.1 These findings indicate that enhancing digital capabilities, strengthening product and service innovation, and fiscal policy support such as government incentives and guidance play a crucial role in boosting MSME performance in East Kalimantan.1 Therefore, collaboration between the government, MSME actors, and financial institutions needs to be strengthened to create an adaptive, innovative, and sustainable business ecosystem.